CROSSINGS OF ANTI-GENDER DISCOURSES IN TEACHERS' ACCOUNTS OF VIOLENCE AGAINST CHILDREN - Spaziani, Raquel Baptista; Lana, Rayanny Zanetti Torquatro de [UNESP] (Univ Fed Sao Paulo, Dept Education, 2024)
This study aimed to analyze the possible reverberations of anti -gender movements in the accounts of elementary school teachers about violence against children, looking to understand their fears and their resistance actions in the classroom. Six teachers from the public school of a capital city and surrounding towns took part in the research, ranging in age from 24 to 47 years. A semi -structured interview script was used, with guiding questions related to perceptions of violence against children, the gender dimensions present in such violence, and the possibility of addressing them in school. The data were analyzed through content analysis, with the following thematic categories: Teachers' perceptions of the relationships between gender and violence against children; Impacts of anti -gender discourses in their accounts; Counter-hegemonic practices and resistance in the classroom. It was seen that the participants seemed to be bothered by attempts to restrict critical work in schools, which further hinders the implementation of actions aimed at sexuality education for children. However, it was noticed that the teachers resisted this logic through actions focused on dialogue with students about gender, sexuality, and violence.
Keywords: Gender; Violence; Childhood